2012
DOI: 10.1159/000338233
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Activities of Daily Living in Alzheimer’s Disease: A Correlational Meta-Analysis

Abstract: Background: The assessment of executive function (EF) and activities of daily living (ADL) are important elements in the diagnosis of Alzheimer’s disease. Methods: Following a comprehensive search in three databases, a random-effects meta-analysis was used to investigate the association between ADL ability and seventeen tests of EF, three tests of attention and working memory and the Mini-Mental State Examination. The association between EF and ADL ability was further investigated in relation to four different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
160
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 175 publications
9
160
3
6
Order By: Relevance
“…More sensitive clinical diagnostic tools might reveal subtle changes in earlier disease stages, including mild AD dementia. For example, while ADAS-Cog and ADCS-iADL showed a good correlation based on current data, a cognitive scale that is more sensitive to executive function may establish an even stronger relationship and greater magnitude of association with activities of daily living [42,43]. An optimized functional measure designed to assess very mild functional change and with culturally neutral elements, might be more applicable to a mildly affected patient population such as the ones studied here and may allow detection of greater magnitude of impact of cognitive impairment on functional impairment.…”
Section: Discussionmentioning
confidence: 58%
“…More sensitive clinical diagnostic tools might reveal subtle changes in earlier disease stages, including mild AD dementia. For example, while ADAS-Cog and ADCS-iADL showed a good correlation based on current data, a cognitive scale that is more sensitive to executive function may establish an even stronger relationship and greater magnitude of association with activities of daily living [42,43]. An optimized functional measure designed to assess very mild functional change and with culturally neutral elements, might be more applicable to a mildly affected patient population such as the ones studied here and may allow detection of greater magnitude of impact of cognitive impairment on functional impairment.…”
Section: Discussionmentioning
confidence: 58%
“…A recent review of studies with older people found that executive functions explain at least three times as much of the variance in IADL as memory [35]. In addition, a recent meta-analysis of studies of people with AD has linked executive function with declining skills and abilities in ADL, suggesting that executive dysfunction may contribute significantly to functional difficulties [36]. In agreement with this findings, higher impairments in multiple-domain MCI than singledomain amnestic MCI have been reported [37].…”
Section: Discussionmentioning
confidence: 99%
“…These need to be factored into the analysis. 11,12 together, take about 10 minutes to complete, with a suggested 20-minute delay. Performance on Logical Memory correlates with outcomes in several neuropsychiatric settings, including recovery from TBI, e13 social functioning in schizophrenia, e14 and the ability to comprehend and reason about treatment decisions in mild to moderate AD.…”
Section: Limitationsmentioning
confidence: 99%
“…These tests are brief, have robust normative values across the adult lifespan, and have been broadly studied in patients with Alzheimer disease (AD) and other cognitive disorders. 11,12 The Corsi Blocks Test 13 involves imitating sequential tapping patterns on blocks arrayed on a board. The longest sequence (i.e., number of blocks) tapped correctly is a measure of spatially mediated attentional capacity.…”
mentioning
confidence: 99%